History of Historiography in the Amazon: the Historical and Geographical Institutes of Pará and Amazonas in constructing a regional historiographic field (1917-1951) - Ferreira Barros, Lucilvana (História da Historiografia: International Journal of Theory and History of Historiography, 2025)
This article is a contribution to Brazilian and Amazonian historiographies regarding the intellectual scenario of the early 20th century, proposing to analyze the role of the Historical and Geographical Institute of Pará (IHGP) and the Geographical and Historical Institute of Amazonas (IGHA) in constructing a regional historiographic field in the Amazon, between 1917 and 1951. The process of creating the historical institutes of the Amazon and the concurrent movement of disciplinary specialization in the region, contributing to the construction of an Amazonian historiographic field, is investigated on journals, chapters, and articles. The initial reading allowed us to understand that the IHGP and IGHA were created in response to the rubber crisis and republican influences. The historians of these institutes institutionalized their productions by publishing in their journals, whose narratives revealed a concern with elaborating a history of Amazonian origins in dialogue with the history of Brazil.